Molecular Characterization of Gβ-Like Protein CpcB Involved in Antifungal Drug Susceptibility and Virulence in A. fumigatus - Cai, Zhendong; Chai, Yanfei; Zhang, Caiyun; Feng, Ruoyun; Sang, Hong; Lu, Ling (Frontiers in Microbiology, 2016)
Aspergillus fumigatus is an airborne human fungal pathogen that can survive in a wide range of environmental condition. G protein complex transduces external signals from a variety of stimuli outside a cell to its interior effectors in all eukaryotes. Gβ-like CpcB (cross pathway control B) belongs to a WD40 repeat protein family with the conserved G-H and W-D residues. Previous studies have demonstrated that Gβ-like proteins cooperate with related signal transduction proteins to function during many important developmental processes. However, the molecular characteristics of Gβ-like CpcB have not yet been identified. In this study, we demonstrated that the G-H residues in WD repeat 1, 2, 3 and the W-D residue in WD repeat 2 are required not only to control normal hyphal growth and conidiation but also to affect antifungal drug susceptibility. The enhanced drug resistance might be due to reduced intracellular drug accumulation and altered ergosterol component. Moreover, we find that the first G-H residue of CpcB plays an important role in the virulence of A. fumigatus. To our knowledge, this is the ﬁrst report for finding the importance of the conserved G-H and W-D residues for a Gβ-like protein in understanding of G protein functions.